Caracterização da interface de tubo bimetálico cladeado fundido por centrifugação - Dessi, João Guilherme (2015)
Bimetallic pipes represent a solution for cost reduction to pipelines in the oil and gas industry, because they combine two materials with distinct characteristics in the pipe manufacturing: a HSLA steel, constituting the external part of the pipe, providing mechanical strength and toughness, and a corrosion resistant alloy (CRA), constituting the internal part of the pipe. Bimetallic pipes can be manufactured by centrifugal casting, which gives a metallurgical bonding between the constituent materials (cladding). The objective of this work was to evaluate the interface of a bimetallic clad pipe produced by centrifugal casting, where the pipe was manufactured externally in HSLA steel (API 5L X65Q) and internally in a Ni-Cr-Mo alloy (Inconel 625) by pouring the two constituent alloys at the same side of the spinning mold. Due the temperature loss along the mold length during the CRA pouring, occurred excessive erosion in the steel close to pouring side of the pipe (hotter side) and just a little appreciable erosion close to the opposite side (colder side), where the defects accumulation prevented a suitable cladding in this region. This erosion promoted an increase of the Fe content of CRA. The as-cast microstructure of the steel in the regions where a satisfactory cladding have been observed in the interface was composed by a decarburized region with the presence of low-carbon bainite adjacent to the interface and polygonal ferrite farther from it. It was possible to combine the solubilization treatment at 1200°C/1h for the CRA and quench treatment followed by tempering necessary to ensure the mechanical properties of the steel as described by the API 5L and 5LD standards, without the occurrence of aging at the CRA. The most suitable tempering treatment have been determined at 650°C/1h, according to the mechanical tests performed at the half-length section of the bimetallic pipe and compared with a monolayer API X65Q pipe as reference.